Conjugation of the ubiquitin-like protein NEDD8 to cullin-2 is linked to von Hippel–Lindau tumor suppressor function - Liakopoulos, Dimitris (The National Academy of Sciences, 1999)
The von Hippel–Lindau tumor suppressor protein pVHL assembles with cullin-2 (hCUL-2) and elongin B/C forming a protein complex, CBC(VHL), that resembles SKP1–CDC53–F-box protein ubiquitin ligases. Here, we show that hCUL-2 is modified by the conserved ubiquitin-like protein NEDD8 and that NEDD8–hCUL-2 conjugates are part of CBC(VHL) complexes in vivo. Remarkably, the formation of these conjugates is stimulated by the pVHL tumor suppressor. A tumorigenic pVHL variant, however, is essentially deficient in this activity. Thus, ligation of NEDD8 to hCUL-2 is linked to pVHL activity and may be important for pVHL tumor suppressor function.